Glycoimmunology - Videira, Paula (Henry Stewart Talks, 2022)
Glycosylation, Glycans and the immune system, Different types of lectins, The role of lectins in immunology, Glycoimmunology in congenital disorders of glycosylation, Glycoimmunology in cancer